KONTEKSTUALISASI KONSEP PEMIMPIN DALAM TEKS HADIS (RIWAYAH, 2018)
Leaders are the main thing in the life of Muslims, without a leader, there will be no direction to the fate of the lives of Muslims in facing the challenges of the world in the future such as economics, social, ecology and so forth. However, the dynamics of problematic Muslim leader concept continue to revolve to determine the concept of interpretation throughout history. The ideal concept of Islamic leaders through studies in the words of deeds, and the provisions of the Prophet Muhammad called Hadith. The author's discussion on the text that the leader in certain cases states must be from the Quraish tribe, the person is male and others related to the concept of leader. In this paper, the author discusses the reality that occurred in the field when the text appeared, that the text is not sacred but dynamic. There is another flexibility of understanding through the contextualization of the hadith that the concept of leader does not have to be from the Quraish tribe and the concept of leader must not be male and other contextual hadith leaders.